The complexity of DLB: U.S.‐based Dementia with Lewy Body Consortium: Biomarkers and early diagnosis of DLB: New findings. (7th December 2020) - Leverenz, James B; Bekris, Lynn M; Berman, Sarah; Fleisher, Jori E; Galasko, Doug R; Galvin, James E; Goldman, Jennifer; Hall, Deborah A; Irwin, David J; Kaufer, Daniel; Lippa, Carol; Litvan, Irene; et al.
Abstract: Background: The clinical syndrome of dementia with Lewy bodies (DLB) is well defined with good positive predictive value for the presence of Lewy body pathology at autopsy. However, the presence of Lewy body pathology in dementia is not always linked to the clinical syndrome of DLB, particularly early in the clinical course (e.g., prodromal and mild cognitive impairment), and co‐pathologies are quite frequent. This clinical and pathologic complexity leads to many challenges including early recognition and diagnosis, clinical management, and development of symptomatic and disease modifying therapies. To address these issues, a number of consortia have been established to longitudinally study DLB and related Lewy body diseases, including a US based Dementia with Lewy Bodies Consortium (DLBC). Method: The U.S.‐based DLBC is a multi‐centered, NIH funded, project to longitudinally and systematically study subjects with DLB and mild cognitive impairment/high likelihood DLB (MCI‐DLB). The primary goal of the DLBC is to generate biospecimens linked to clinical, imaging, and neuropathologic characterization in a longitudinally followed cohort across the participating DLBC sites. Biofluids, including blood and cerebrospinal fluid (CSF), and data generated by the DLBC will be ultimately be available to investigators through the NINDS‐funded Parkinson's Disease Biomarker Program. Result: To date, one hundred and thirteen subjects have been enrolled in the DLBC. Preliminary results from the first ninety‐two subjects note a male predominance in the sample (82 of 92, 89%). At baseline visit, mean age was 69.4 (SD 7.1 years), baseline UPDRS‐MDS Part III was 28.9 (15.7 SD) and MoCA 20.4 (SD 5.4). Neuropathologic data are limited, but suggest that an elevated CSF p‐tau may assist in clinically differentiating DLB with or without high levels of Alzheimer's disease pathology. Imaging results including volumetric MRI, amyloid imaging and DaTscan are pending. Conclusion: The development of DLB cohorts, such as the US based DLBC, is essential to understanding the complexity and pathobiologic significance of the clinical syndrome, biomarker characteristics and imaging findings in patients with underlying Lewy body disease. These results continue to emphasize the importance of further development of biomarkers in DLB and related neurodegenerative disorders.